Effects of different supplementary cementitious materials on the performance and environment of eco-friendly mortar prepared from waste incineration bottom ash. (21st November 2022) - Fan, Xu; Li, Zhenlin; Zhang, Weizhuo; Jin, Hesong; Chen, Chaoyun; Liu, Jun; Xing, Feng; Tang, Luping
Highlights: The leaching amounts of Cu and Zn in MSWIBA were 2.53 and 18.28 mg/kg, which were higher than the US EPA regulations. Eco-friendly mortar can reduce the leaching amount of harmful elements in MSWIBA by more than one time. Compared with traditional mortar, the eco-friendly mortar can reduce energy consumption, CO2 emission and cost. Eco-friendly mortar can effectively recycle large quantities of MSWIBA. Different supplementary cementitious materials can improve the mechanical properties of eco-friendly mortar. Abstract: Municipal solid waste incineration bottom ash (MSWIBA) is a by-product produced by municipal waste incineration treatment. In this study, MSWIBA particle size distribution, chemical composition and particle shape were investigated and confirmed its value for reuse in the construction field and its good research potential. MSWIBA was used as fine aggregates, while coal fly ash (FA) and ground granulated blast furnace slag (GGBFS) were used as auxiliary cementitious materials to replace part of cement to manufacture the eco-friendly mortar (EFM). The effect of FA/GGBFS on the mechanical and microscopic properties of EFM with different material ratios was mainly investigated. And the analysis of the environmental friendliness and economy of this EFM was made. The results show that the combination of FA and GGBFS at the same time reduces the early mechanical properties of the mortar. However, the strength developed rapidly after 7 days, with an increase of more than 6 times the rate before 7 days. Compared with GGBFS, FA is more helpful in improving the mechanical properties of the EFM. After 28 days of full hydration, the hydration products within the EFM are numerous and well bonded to each other. Not only do these hydration products increase the mechanical strength of EFM, but they also successfully solidify the hazardous components in MSWIBA and reduce their negative environmental effects. In addition, the use of MSWIBA instead of sand for mortar preparation reduces energy consumption and CO2 emissions, and it reduces the cost by more than 50 %. This indicates that MSWIBA may perform well in the future development of the civil infrastructures. As well as recycling waste resources, it makes a valuable contribution to the development of green and sustainable building materials.